The advantages and disadvantages of the popular democracy orientation of community organizing work to the National Democratic Movement - Sagayo, Jerry P. (Quezon City : St. Andrew's Theological Seminary, 1989)
The paper seeks to present the pros and cons of the Popular Democracy Project to the National Democratic Struggle. With Parola as the area of study, the paper would further be comprehensive as it would relate the organizing work to the broader political spectrum.
A paper presented to the faculty of Saint Andrew's Theological Seminary
In partial fulfillment of the requirements for the degree of Bachelor in Theology
Thesis (B.Th.)-- St. Andrew's Theological Seminary